Low‐frequency harmonic resonance analysis and suppression method of modular multilevel converter. Issue 4 (1st April 2018) - Yue, Yufei; Xu, Qianming; Shuai, Zhikang; He, Zhixing; Guo, Peng; Li, Yan; Luo, An; Shen, John
Abstract : Modular multilevel converters (MMCs) become increasingly attractive in high‐voltage dc (HVDC) transmission systems. However, the internal poorly damped characteristic can easily lead to low‐frequency harmonic resonance, affecting the stability of MMC. In this study, the equivalent model of MMC is established to reveal the low‐frequency harmonic resonance, including intrinsic harmonic resonance and potential harmonic resonance. To suppress the harmonic resonance, a circulating current suppressing method based on active damping is proposed to improve the internal damped characteristic. In order to enhance the control effectiveness, the circulating current reference is modified through a dual feedback closed‐loop control involving arm voltages and currents as well as the power feedforward loop in the proposed suppression strategy. Proper parameters are designed to apply the reasonable damping characteristic of MMC. Finally, the proposed method is implemented and verified with an MMC‐HVDC system in the RT‐LAB simulator platform.